BUNJEVCI IN SERBIA – CROATS, SERBS OR SPECIFIC ETHNIC COMMUNITY - Raduški, Nada (Political Review, 2023)
The paper analyzes the ethno–demographic, identity and political development of the people of Bunjevci in Serbia. Numerous theories of ethnologists, historians, linguists and sociologists of religion about the origin, language and religion of the people of Bunjevci were presented, as well as the ethno–political development of the Bunjevci people, throughout history until today, by confronting different attitudes and answers to the question: are the Bunjevci more Serbs, Croats or a specific national community? The importance of national self–identification, i.e. the free declaration of the people of Bunjevci about their own national identity and the impact of changes during the census declaration on their population development, was highlighted. Viewed over time, the political development of the Bunjevci national minority in Serbia is characterized by turbulent changes, from denial to recognition of their national and cultural distinctiveness, the struggle not to assimilate into either the Croatian or the Serbian nation, which became a feature of their identity and preserved this ethnic community until today. Predictions are that the Bunjevac national minority in Serbia, without the formation of a modern socio–economic structure and cultural–political institutions, is in danger of disappearing by the end of the 21st century, like all other small linguistic communities, according to the opinion of many domestic and international expert. For the survival, demographic and cultural development of Bunjevci as a modern ethnic community, activities that contribute to the integration of the Bunjevci people and establish equal relations with all other ethnic communities, as well as with the wider socio–political environment, are necessary. For Bunjevci, as a long–disenfranchised and “erased” national community, the affirmation of one's own ethnic, linguistic and cultural identity is an important prerequisite for achieving equality and social integration as a special minority community. This primarily refers to the contestation and appropriation of everything that belongs to the Bunjevci by the Croatian national community in Vojvodina, as well as efforts to assimilate into the borders of Serbian culture and history. However, the accepted principles of multiculturalism in Serbia form the basis and guarantee for the affirmation of the Bunjevci people as a small nation and a chance for their overall faster development, for the preservation and improvement of all components of their ethnic identity, as well as full equality, both with the majority people and with all other nationalities in Serbia.
Keywords: Bunjevci; identity; language; religion; demographic and political development; Serbia